Bimbingan Kelompok Menggunakan Media Visual Art untuk Meningkatkan Self Efficacy Peserta Didik di SMP Negeri 16 Palembang - Lendi Marsela; Evia Darmawani; Syska Purnama Sari (Departement of Mathematics Education, 2024)
Self efficacy affects the way a person thinks, motivates himself and acts. The problem in this study is that there are still students who do not complete assignments, easily give up when they encounter difficulties and have never carried out group guidance using visual art media. The goal to be achieved in this study is to determine the effectiveness of group guidance services using visual art media in increasing student self-efficacy. This study uses a quantitative method Pre-Experiment (Pre-Experiment Design, One Group Pretest-Posttest Design). The research subjects were class VIII7 students with a population of 32 students, and a total sample of 8 students. The sampling technique uses purposive sampling, this technique is not sampling on strata, random, but based on research objectives. From the results of research and data analysis, it shows that there is an increase in the self-efficacy of students after being given treatment of group guidance services using visual art media as evidenced by the results of a high increase in self-efficacy scores from 49% to 74%, this is also confirmed from the results of the Wilcoxon test with a significant 0.012 which means 0.012> 0.05, the hypothesis in this study is accepted. So it can be concluded that group guidance using visual art media is effective in increasing the self-efficacy of students at SMP Negeri 16 Palembang. Keywords: self-efficacy, group conseling, visual art.